Strategi Media Alternatif Proyek Multatuli dalam Menjaga Keberlangsungannya - Muhammad Afriski Nanda Pradana; Eni Maryani; Sri Seti Indriani (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This research aims to provide an in-depth analysis of Project Multatuli as an alternative media outlet, focusing on both organizational and editorial perspectives. It also explores the challenges faced by such alternative media organizations. The findings reveal that Project Multatuli, at a fundamental level, can be regarded as critical alternative media that meets the criteria outlined by Sandoval and Fuchs. As an alternative media outlet, Project Multatuli relies on funding from donors, grants, and initiatives from "Kawan M" to cover its operating costs. Its news cycle adheres to the principles of "painstaking journalism," with coverage that typically spans two to three months. Project Multatuli holds transparency in high regard, consistently disclosing its funding sources, whether they support specific reports or provide the initial inspiration for news coverage. Distinct from mainstream media, Project Multatuli operates similarly to a Non-Governmental Organization (NGO).